STUDI SEMANTIK KOGNITIF DALAM KUMPULAN FANFICTION RIDDLE - Irma Yuliana (Universitas Lambung Mangkurat, 2019)
nalin_lee@yahoo.comAbstractCognitive Semantic Studies in The Fanfiction Riddle Collection. The studydiscusses the semantic cognitive studies in the fanfiction Riddle Group.There are 13 fanfiction riddle taken from the site http://www.indofanfictkpop.wordpress.com used as a source ofresearch. The study uses a cognitive semantic approach. The method used is content analysis. The techniques used to collect data are documentation techniques (literature studies). Based on the method used then the technique of data processing by reading intensively then analyze the facts. As a result of this research, researchers found that the answer to riddle comes from asemantic cognitive reading process sourced from